Observational Study on Hematological Adverse Drug Reactions (HADRs) from Hydroxyurea in Pediatric Patients with Sickle Cell Disease (SCD): Assessing Prevalence, Causality, Severity, Preventability, and Predictability, along with Clinical Management by a Clinical Pharmacist at a Tertiary Care Teaching Hospital - Rajesh Hadia; Rajesh Maheshwari; Dipika Bhil (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Hydroxyurea therapy is crucial in managing sickle cell disease (SCD) in pediatric patients, significantly reducing vaso-occlusive events. However, it is associated with hematological adverse drug reactions (HADRs), necessitating comprehensive evaluation to ensure patient safety and treatment optimization. Objective: The primary goal of our study is to investigate the prevalence, causality, severity, preventability, and predictability of HADRs associated with hydroxyurea therapy in pediatric patients with SCD. Materials and Methods: A prospective observational study was conducted, involving 207 pediatric SCD patients undergoing hydroxyurea therapy. Data were collected from medical records and adverse drug reaction reporting forms. Causality, severity, preventability, and predictability assessments were conducted using standardized tools. Results: The prevalence of HADRs was 7.24%, with neutropenia (2.41%) and thrombocytopenia (1.93%) being the most common. Gender-specific prevalence rates, age distribution, and in-patient versus out-patient settings showed consistent patterns. Causality assessment revealed a high proportion of probable or certain HADRs. The majority of HADRs were of mild to moderate severity and considered preventable. Finding: Hydroxyurea therapy in pediatric SCD patients is associated with manageable HADRs, emphasizing the importance of pharmacovigilance for patient safety and treatment compliance. Conclusion: This study offers significant insights into the prevalence, clinical management, and outcomes of HADRs associated with hydroxyurea therapy in pediatric SCD patients. The findings underscore the need for proactive management approaches to optimize treatment outcomes and ensure patient safety.